Synthesis and Characterization of New Conjugated Polymers Based on Furan Ring from D-fructose and Their Photoluminescence and Thermal Properties - Hanoon, Wael Sadiq; Hanoosh, Widad Salih; Zaidan, Raed Kadim (Indonesian Journal of Chemistry, 2025)
Conjugated polymers are one of the most essential branches of polymer science. Most conjugated polymers have a small band gap energy between the ground state and excited state, making them fluorescent materials useful for use as light emitting diodes (LED), sensors, digital screens, and others. We synthesized dialdehyde compound (F1) with good yield and high quality from a natural source (D-fructose) and characterized by proton nuclear magnetic resonance (1H-NMR), carbon-13 nuclear magnetic resonance (13C-NMR), electron impact (EI) mass spectra, and Fourier-transform infrared spectroscopy (FTIR). We synthesized two salts of disubstituted benzene triphenylphosphonium chloride (W1, W2) and characterized them by 1H-NMR and FTIR. We synthesized two polymers by Wittig polycondensation from the reaction of F1 with salts (W1, W2) and characterized by 1H-NMR, FTIR spectroscopy and gel permeation chromatography (GPC). Their photoluminescence properties were studied which giving light emission with λPL max at 502 and 472 nm for A1 and A2, respectively. We synthesized three polymers (P1, P2, P3) from reacting F1 with ketone by aldol condensation using KOH to give insoluble polymers and characterized them by FTIR spectroscopy. All polymers were evaluated by thermal gravimetric analysis (TGA), showing thermal stability with decomposition temperature beginning from 192 °C.